Camera Trapping Medium to Large Mammals in Selected Areas within Pasin Forest Management Unit, Sarawak - Erick, Paranjothi Yanok (Universiti Malaysia Sarawak, (UNIMAS), 2022)
This study was conducted in Pasin Forest Management Unit (FMU) in Song Sarawak from 1st January 2016 to 6 th July 2020 to determine the activity pattern of medium to large mammals in the area, and the activity pattern of sympatric species differs. A total of 1,649 days of camera trapping yielded 3,848 photos, and 18 different medium to large mammal species were recorded. Banded palm civet, Hemigalus derbyanus, records the highest independent event obtained, 70 independent events, followed by Pig-tailed macaque, Macaca nemestrina, with 66 independent events. Sunda pangolin, Manis javanica, which is critically endangered on the IUCN list and the presence of the rare Hose's palm civet, Diplogale hosei, were recorded in this study. The activity pattern of four mammals wasstudied, and it was found that the Pig-tailed macaque, Macaca nemestrina, exhibits a diurnal behaviour. At the same time, Malayan porcupine, Hystrix brachyura, Malay civet, Viverra tanglunga, and Banded palm civet, Hemigalus derbyanus show a nocturnal behaviour. The activity pattern between sympatric species Banded palm civet, Hemigalus derbyanus and Malay civet, Viverra tanglunga, shows an overlap of 0.45 in overlap coefficient. The overlap activity pattern between pig-tailed macaque, Macaca nemestrina, and long-tailed macaque, Macaca fascicularis, also shows an overlap of 0.45 in the overlap coefficient. Constant monitoring of the area should be carried out to prevent illegal poaching of rare mammals in the area. More cameras should be deployed for an extended period to obtain a better insight into the species present in Pasin FMU.